Un chien andalou . Andalusian Dog - Buñuel, Luis (France, 1929)
In a dream-like sequence, a woman's eye is slit open--juxtaposed with a similarly shaped cloud obsucuring the moon moving in the same direction as the knife through the eye--to grab the audience's attention. The French phrase "ants in the palms," (which means that someone is "itching" to kill) is shown literally. A man pulls a piano along with the tablets of the Ten Commandments and a dead donkey towards the woman he's itching to kill. A shot of differently striped objects is repeatedly used to connect scenes.